Cell surface hydrophobicity and colony morphology of Trichosporon asahii clinical isolates. Issue 3 (2nd December 2016) - Ichikawa, Tomoe; Hirata, Chihiro; Takei, Mizuki; Tagami, Naoyuki; Murasawa, Hiromi; Ikeda, Reiko
Abstract: Trichosporon asahii is a pathogenic basidiomycetous yeast. Individual strains of T . asahii have different colony morphologies. However, it is not clear whether cell surface phenotypes differ among the colony morphologies. Here we characterized the cell surface hydrophobicity and analysed the carbohydrate contents of the cell surface polysaccharides in T . asahii clinical isolates with various colony morphologies. Among the three distinctive colony morphologies obtained from one clinical isolate, the white‐type morphology exhibited higher hydrophobicity. The hydrophobicity of heat‐killed T . asahii cells was greatly reduced after periodate oxidation of the cell surface carbohydrates. Furthermore, the cell wall and extracellular polysaccharide components differed among the morphologies. Our results suggest that T . asahii cell surface hydrophobicity is affected by cell surface carbohydrate composition. Copyright © 2016 John Wiley & Sons, Ltd.